Fuzzy pre-continuous and fuzzy pre*-continuous function of fuzzy pre-compact space in fuzzy topological space - Al-Khafaji, Munir Abdul Khalik; Hasan, Marwah (International Journal of Advanced Mathematical Sciences, 2015)
The aim of this paper is to introduce and study the notion of a fuzzy pre-continuous function, fuzzy pre*- continuous function, fuzzy pre-compact space and some properties, remarks related to them.